LOW BIRTH WEIGHT AND BIRTH LENGTH AS DETERMINING FACTORS FOR STUNTING CHILDREN AGED 9-23 MONTHS IN INDONESIA [ANALYSIS OF 2018 BASIC HEALTH RESEARCH DATA] - Khasanah, Dwi Puji; Ani Margawati; Rosidi, Ali; Rahfiludin, Mohammad Zen; Noer, Etika Ratna (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Stunting remains a prevalent health issue among children under two years old in Indonesia. The nutritional status of newborns, indicated by birth weight and length, is crucial for neonatal development. Malnutrition in neonates can lead to increased mortality rates, neurological and cognitive impairments, and stunting. This study aims to identify the risk factors associated with stunting among children aged 9-23 months in Indonesia, utilizing data from the 2018 Basic Health Research. The study design was cross-sectional. This study examined a sample of 7,396 children within the specified age group. The study reveals a stunting prevalence of 30.4% among children aged 9-23 months. Logistic regression analysis indicates that low birth weight (LBW) (AOR 1.854; 95% CI 1.50-2.30), birth length (AOR 1.550; 95% CI 1.37-1.74), and male gender (AOR 1.272; 95% CI 1.15-1.41) are significant risk factors associated with stunting in this age group. Therefore, addressing these factors is crucial for combating stunting among children under two years old in Indonesia.